Effect of employee background on perceived organizational justice: managerial implications. (June 2014) - Tessema, Mussie T; Tsegai, Goitom; Ready, Kathryn; Embaye, Abel; Windrow, Brian
The study examines the effect employee background (gender, education level and affiliation to the government) on organizational justice perceptions using the three-factor model (distributive, procedural and interactional justice). Selected demographic and attitudinal data were collected from a sample of 313 employees representing 10 public organizations. The findings of this study show that gender had a significant effect on distributive and interactional justice but not procedural justice; education level had a significant effect on distributive and procedural justice but not interactional justice; and affiliation to the government had a significant effect on all the three dimensions of justice. Managerial implications of these findings and future research directions are also discussed. Points for practitioners: Gaining a better insight into the effects of demographic factors (gender, education level and affiliation to the government) on the three dimensions of organizational justice indicates to policymakers and public managers where improvements can be made, and helps them to develop strategies and policies that could improve the perceived justice. Another important implication of this study for countries emerging from a civil war, liberation struggle or other similar conflict (for example, South Sudan, Libya, Afghanistan) is regarding converting former fighters into civil servants and their management afterwards. It is crucial to provide them employment opportunities in a civil service provided that they are placed based on the principle of the right persons on the right positions and then treat them as equal as their counterparts: non-ex-fighter civil servants. They only need to be given some (special) kind of training (at the beginning) that expedites their socialization and integration into the main stream way of thinking and doing things.